Kyrgyz Republic Public Expenditure Review Policy Notes : Public Wage Bill - World Bank (Washington, DC, 2014)
Restraining the growing wage bill expenditures while enhancing the performance of the public sector remains one of the government's major development priorities. Wage bill levels in the Kyrgyz Republic are high compared to the majority of Europe and Central Asia (ECA) countries, constituting almost one third of government expenditures. Over the last few years, the government has undertaken important steps towards enhancing pay systems and improving competitiveness of pay in public health and education sectors accounting for almost 66 percent of the wage bill. The Kyrgyz Republic confronts the need to restrain its public wage bill as part of its mid-term fiscal strategy, as well as the need to improve the performance of the public sector. The analysis, undertaken in this policy note, suggests that the government should consider the following measures and reforms: improve predictability of the wage bill and avoid further ad hoc increase in wages; moderate and gradual consolidation of employment; any increase of the base pay elements has to be linked to modest and gradual consolidation of public sector employment, and should be limited to inflation as needed; establishment controls need to be strengthened through sound monitoring of the number of employees and payroll in all parts of the public sector; and civil service pay reform has to be undertaken with a unified pay system, gradually introduced at all levels of the government. This note discusses public sector wage management in the Kyrgyz Republic, by analyzing wage bill expenditure levels over the last decade with a closer examination of dynamics in 2008-2011.